2022
DOI: 10.1186/s40854-022-00395-w
|View full text |Cite
|
Sign up to set email alerts
|

Time–frequency co-movement and risk connectedness among cryptocurrencies: new evidence from the higher-order moments before and during the COVID-19 pandemic

Abstract: Analyzing comovements and connectedness is critical for providing significant implications for crypto-portfolio risk management. However, most existing research focuses on the lower-order moment nexus (i.e. the return and volatility interactions). For the first time, this study investigates the higher-order moment comovements and risk connectedness among cryptocurrencies before and during the COVID-19 pandemic in both the time and frequency domains. We combine the realized moment measures and wavelet coherence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 129 publications
3
12
0
Order By: Relevance
“…This result is consistent with the findings of Finta and Aboura ( 2020 ), who document the prominent role of volatility risk premium in spillovers among the U.S., U.K., German, and Japanese stock markets. Our result further corroborates several previous studies that find that the realized volatility spillover is stronger than the spillovers in skewness and kurtosis (Cui and Maghyereh 2022 ; Hasan et al 2021 ; Bouri et al 2021d ; Yi et al 2018 ).…”
Section: Empirical Analysissupporting
confidence: 92%
“…This result is consistent with the findings of Finta and Aboura ( 2020 ), who document the prominent role of volatility risk premium in spillovers among the U.S., U.K., German, and Japanese stock markets. Our result further corroborates several previous studies that find that the realized volatility spillover is stronger than the spillovers in skewness and kurtosis (Cui and Maghyereh 2022 ; Hasan et al 2021 ; Bouri et al 2021d ; Yi et al 2018 ).…”
Section: Empirical Analysissupporting
confidence: 92%
“…They report that there is a moderate liquidity connectedness among six major cryptocurrencies, with Bitcoin and Litecoin playing a significant role concerning the magnitude of connectedness. Moreover, Cui and Maghyereh ( 2022 ) study the higher-order moment co-movements and risk connectedness among cryptocurrencies before and during the COVID-19 pandemic. Lorenzo and Arroyo ( 2022 ) describe, summarize, and segment the main trends of the cryptocurrency market in 2018.…”
Section: A Summary Of the Special Issue Papersmentioning
confidence: 99%
“…For example, to extend the study of Hasan et al ( 2022 ), future research may explore the determinants of liquidity connectedness in the cryptocurrency market. To extend Cui and Maghyereh ( 2022 ), future research can investigate the higher-order moment portfolio optimizations of cryptocurrencies. Another promising research direction is to examine the extreme risk connectedness among cryptocurrencies from a time–frequency domain perspective.…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…On the other hand, other studies have found that these emerging blockchain-based tokens are merely correlated with high volatility in times of crisis, such as during COVID-19 (Maouchi et al, 2022). A pioneering study on DeFi tokens' behavior revealed that they could be considered a distinct asset class from cryptocurrencies (Corbet et al, 2022).…”
Section: Introductionmentioning
confidence: 98%